Impact of farmer-managed natural regeneration on resilience and welfare in Mali - Nkonya, Ephraim M.; Kato, Edward; Kabore, Carolyn (Bon View Publishing Pte Ltd., 2024)
Climate change, poverty, and low environmental education have contributed to increasing vulnerability of poor farmers in Mali. This study was done to determine the impact of low-cost adaptation strategies on resilience and welfare. We analyzed the impact of a World Vision project which promoted climate-smart agricultural (CSA) practices in Mali from 2016-2019. We identified the impact using a two-stage weighted regression (2SWR). Results show that the World Vision Project significantly increased the adoption of Farmer-Managed Natural Regeneration (FMNR) practice and eventually crop yield. These intermediate impacts were translated into a significant reduction in food and nutrition insecurity and an increase in household income. The impacts of the project on child health were especially greater for farmers who participated in the project for a longer time. However, the project did not have a significant impact on the adoption of a combination of CSA practices – which could have enhanced the effectiveness of the FMNR practice. The results suggest the need for future interventions to emphasize the promotion of complementary CSA practices, which significantly increases returns to farmer investments.